2017
DOI: 10.1214/16-aos1476
|View full text |Cite
|
Sign up to set email alerts
|

Network vector autoregression

Abstract: We consider here a large-scale social network with a continuous response observed for each node at equally spaced time points. The responses from different nodes constitute an ultra-high dimensional vector, whose time series dynamic is to be investigated. In addition, the network structure is also taken into consideration, for which we propose a network vector autoregressive (NAR) model. The NAR model assumes each node's response at a given time point as a linear combination of (a) its previous value, (b) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Consequently, techniques used for HMM cannot be applied here. Instead, the same setting as in Zhu et al (2017) is considered, thus, the process X as well as the network Ad is observed; we have observations X 1 , . .…”
Section: Statistical Results For Doubly Stochastic Network Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, techniques used for HMM cannot be applied here. Instead, the same setting as in Zhu et al (2017) is considered, thus, the process X as well as the network Ad is observed; we have observations X 1 , . .…”
Section: Statistical Results For Doubly Stochastic Network Processesmentioning
confidence: 99%
“…Consequently, a more radical approach needs to be applied here in order to reduce the number of parameters. Here we adapt the idea of model (2.1) in Zhu et al (2017). The model reads as follows:…”
Section: Statistical Results For Doubly Stochastic Network Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…High-dimensional time series is one of the most common types of "big data" and can be found in many areas including meteorology, genomics, finance and economics (Hallin and Lippi, 2013). The classical vector autoregressive (VAR) model is fundamental to multivariate time series modeling and has recently been applied to the high-dimensional case under certain structural assumptions, e.g., the banded structure (Guo et al, 2016) and the network structure (Zhu et al, 2017). Consider the VAR model of the form (Lütkepohl, 2005;Tsay, 2010):…”
Section: Introductionmentioning
confidence: 99%